CD24 Gene Polymorphism - A Novel Prognostic Factor in Esophageal Cancer. Issue 1 (January 2014) - Sadot, Eran; Kraus, Sarah; Stein, Michael; Naboishchikov, Ilana; Toledano, Ohad; Kazanov, Dina; Arber, Nadir; Kashtan, Hanoch
Background: The CD24 gene has been correlated with poor prognosis of various malignancies. The significance of CD24 in esophageal cancer remains unknown. Our aim was to evaluate the association between CD24 genetic polymorphism and esophageal cancer. Materials and Methods: Between June 2011 and May 2012 patients with esophageal cancer and healthy controls were prospectively enrolled and clinicopathological data were collected. Genomic DNA was extracted and restriction fragment length polymorphism (RFLP) analysis was performed to determine CD24 polymorphism at the coding region of CD24, which results in a substitution of the amino acid Ala by Val. Statistical significance was determined by unpaired t -test, χ 2 -test, and Fisher's exact test. Results: A total of 102 patients were included, of whom 51 had esophageal cancer and the rest comprised a healthy control group. The incidence of the polymorphism variant (Val/Val) among the healthy subjects and the esophageal cancer cohort was 6% in both groups. The incidence of N3 (metastasis in 7 or more regional lymph nodes) was markedly higher in those esophageal cancer patients who carried the polymorphism variant compared with those who did not carry it (66% and 2%, respectively, p=0.007). No significant difference was found between the groups with regard to age, gender, histology type, tumor location, tumor stage, and other histological characteristics of the tumor. Conclusions: This CD24 polymorphism may serve as a novel prognostic marker identifying esophageal cancer patients with poor prognosis. Further studies are warranted to evaluate CD24 function and to validate its predictive potential with regard to esophageal cancer.